2014
DOI: 10.1089/cell.2014.0003
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Cloned Embryos Development by Co-Culturing with Parthenotes: A Possible Role of Exosomes/Microvesicles for Embryos Paracrine Communication

Abstract: It is well known that embryos cultured in a group can create a microenvironment through secretion of autocrine and paracrine factors that can support and improve the embryos' development when compared to the embryos cultured individually. In this study, we used a co-culture system for paracrine communication between different kinds of embryos. The results showed that co-culture of porcine parthenogenetic (PA) embryos significantly improved the in vitro development of cloned (nuclear transfer, NT) embryos. To r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
145
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 139 publications
(161 citation statements)
references
References 79 publications
(78 reference statements)
13
145
1
2
Order By: Relevance
“…Also, transcripts for OCT4, KLF4 and NANOG were identified in extracellular vesicles isolated from the cell culture media of PA embryos; additionally, levels of these transcripts were increased in NT embryos following the co-culture with PA embryos. Furthermore, it was demonstrated that these extracellular vesicles could be up take by NT embryos independent of the zona pellucida presence, demonstrating that these vesicles are capable of crossing this structure (SAADELDIN et al, 2014). Thus, these results demonstrate that extracellular vesicles can mediate cell communication and improve embryo development in vitro during the preimplantation period.…”
Section: Epigenetic Mechanisms Of Natural Reprogramming Versus Cloningmentioning
confidence: 60%
See 2 more Smart Citations
“…Also, transcripts for OCT4, KLF4 and NANOG were identified in extracellular vesicles isolated from the cell culture media of PA embryos; additionally, levels of these transcripts were increased in NT embryos following the co-culture with PA embryos. Furthermore, it was demonstrated that these extracellular vesicles could be up take by NT embryos independent of the zona pellucida presence, demonstrating that these vesicles are capable of crossing this structure (SAADELDIN et al, 2014). Thus, these results demonstrate that extracellular vesicles can mediate cell communication and improve embryo development in vitro during the preimplantation period.…”
Section: Epigenetic Mechanisms Of Natural Reprogramming Versus Cloningmentioning
confidence: 60%
“…Cellsecreted vesicles containing bioactive molecules such as miRNA, mRNA and proteins have been shown to mediate cell communication among different cell types (BURNS et al, 2014;. Recently, an experiment demonstrated the transfer of cell-secreted vesicles from parthenogenetic embryos to cloned embryos, providing a new paradigm for embryo-to-embryo communication in vitro (SAADELDIN et al, 2014). Herein, this review presents new perspectives on the role of cell-secreted vesicles during female gamete development as well as during pre-implantation period.…”
Section: Epigenetic Mechanisms Of Natural Reprogramming Versus Cloningmentioning
confidence: 98%
See 1 more Smart Citation
“…However, the use of this technique is limited owing to its low efficiency and several trials showed the improvement of cloning efficiencies [9]. Therefore, the current issue of "Cloning & Transgenesis" will focus on cloning and semi-cloning regarding the trials to improve their efficiency and to reveal their potential applications in biology and medicine.…”
Section: Editorialmentioning
confidence: 99%
“…Members of the TGFβ superfamily, including TGFβ1, TGFβ3, bone morphogenetic protein 15 (BMP15) and growth differentiation factor 9 (GDF9), are expressed in the oocyte from very early stages and are responsible for oocyte maturation (da Silveira et al 2014). Further, few studies have focused on the effects of exposure to a combination of growth factors on oocyte IVM (Arat et al 2016), but the co-culture system also chosen to support the IVM condition (Saadeldin et al 2014;Appeltant et al 2016).…”
Section: Introduc Onmentioning
confidence: 99%